2022
DOI: 10.3390/en15010332
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renewable Energy Sources on the Economic Growth of Poland and Sweden Considering COVID-19 Times

Abstract: A demonstration of the relationship between the share of renewables in gross marginal energy and selected countries’ economic growth is the basis of this research. The paper seeks to investigate mutual correlations between renewable energy sources and economic growth for two EU economies and how it influences their fluctuations (increase and decrease). The comparative analysis of results was carried out for less-income Polish and high-income Swedish economies. This research used a regression model to answer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Fiscal economic reforms, including financial reforms on long-term spending, improved healthcare outcomes, increased life satisfaction, and increased government trust [ 30 ]. The current literature is related to the vulnerability of the coronavirus to different sectors, including renewable energy [ 31 ], higher education [ 32 ], environmental quality [ 33 ], public health [ 34 ], SMEs [ 35 ], and the stock return of pharmaceutical companies [ 36 ]. These studies, in general, concluded that economic activity was mainly depressed during the wake of the COVID-19 pandemic; hence, it is imperative to minimize coronavirus cases to support growth-driven activities worldwide.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Fiscal economic reforms, including financial reforms on long-term spending, improved healthcare outcomes, increased life satisfaction, and increased government trust [ 30 ]. The current literature is related to the vulnerability of the coronavirus to different sectors, including renewable energy [ 31 ], higher education [ 32 ], environmental quality [ 33 ], public health [ 34 ], SMEs [ 35 ], and the stock return of pharmaceutical companies [ 36 ]. These studies, in general, concluded that economic activity was mainly depressed during the wake of the COVID-19 pandemic; hence, it is imperative to minimize coronavirus cases to support growth-driven activities worldwide.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Menyah and Wolde-Rufael ( 2010), for example, find evidence of one-way causality between GDP growth and the utilisation of renewable energy in the United States. Conservation theory was also validated by more recent studies (see e.g., Chen et al, 2022;Islam et al, 2022;Slusarczyk et al, 2022).…”
Section: Conservation Hypothesismentioning
confidence: 74%
“…The separation in higher susceptible groups demonstrates a substantial variation since the COVID-19 was initiated in nine of the twelve urban areas. Previous literature has mostly referred to mobility as asset that wealthier residents may be better equipped or socially situated to escape their neighborhood and enjoy amenities and social mixing in more advantaged areas, whereas more disadvantaged residents may be more bounded to the neighborhood (Ślusarczyk et al 2022 ). Social network study has indicated that close relatives are likely to live close to one another, with minority groups such as Black and Mexican Americans more likely to live with their kin than White people (Irfan et al 2021b ).…”
Section: Resultsmentioning
confidence: 99%